Transcriptional profiling of the leaves of near-isogenic rice lines with contrasting drought tolerance at the reproductive stage in response to water deficit - Moumeni, A.; Satoh, K.; Venuprasad, R.; Serraj, R.; Kumar, A.; Leung, H.; Kikuchi, S. (Springer, 2015)
Drought tolerance is a complex quantitative trait that involves the coordination of a vast array of genes belonging to different pathways. To identify genes related to the drought-tolerance pathway in rice, we carried out gene-expression profiling of the leaves of near-isogenic lines (NILs) with similar genetic backgrounds and different set of QTLs but contrasting drought tolerance levels in response to long-term drought-stress treatments. This work will help differentiate mechanisms of tolerance in contrasting NILs and accelerate molecular breeding programs to improve drought tolerance in this crop. The two pairs of rice NILs, developed at the International Rice Research Institute, along with the drought-susceptible parent, IR64, showed distinct gene-expression profiles in leaves under different water-deficit (WD) treatments. Drought tolerance in the highly drought-tolerant NIL (DTN), IR77298-14-1-2-B-10, could be attributed to the up-regulation of genes with calcium ion binding, transferase, hydrolase and transcription factor activities, whereas in the moderate DTN, IR77298-5-6-B-18, genes with transporter, catalytic and structural molecule activities were up-regulated under WD. In IR77298-14-1-2-B-10, the induced genes were characterized by the presence of regulatory motifs in their promoters, including TGGTTAGTACC and ([CT]AAC[GT]G){2}, which are specific to the TFIIIA and Myb transcription factors, respectively. In IR77298-5-6-B-18, promoters containing a GCAC[AG][ACGT][AT]TCCC[AG]A[ACGT]G[CT] motif, common to MADS(AP1), HD-ZIP, AP2 and YABBY, were induced, suggesting that these factors may play key roles in the regulation of drought tolerance in these two DTNs under severe WD. We report here that the two pairs of NILs with different levels of drought tolerance may elucidate potential mechanisms and pathways through transcriptome data from leaf tissue. The present study serves as a resource for marker discovery and provides detailed insight into the gene-expression profiles of rice leaves, including the main functional categories of drought-responsive genes and the genes that are involved in drought-tolerance mechanisms, to help breeders identify candidate genes (both up- and down-regulated) associated with drought tolerance and suitable targets for manipulating the drought-tolerance trait in rice.